Answer:
9, 11, 13
Step-by-step explanation:
The integers are x, (x+2), and (x+5).
9(x + 4) = (x+2)^2 - 4
9x + 36 = (x+2)(x+2) - 4
9x + 36 = x^2 + 4x + 4 - 4
9x + 36 = x^2 + 4x
Subtract x^2 + 4x from both sides
-x^2 + 9x - 4x + 36 = 0
-x^2 + 5x + 36 = 0
Divide each side by -1
x^2 - 5x - 36 = 0
Factor
(x+4)(x-9) = 0
Solve
-4 + 4 = 0 and 9 - 9 = 0
Since it is positive and odd exponents, x will not be 4, it will be 9.
x = 9 9 + 2 = 11 9 + 4 = 13
9, 11, 13
-------------Check-------------
9(x + 4) = (x + 2)^2 - 4
9(9 + 4) = (9 + 2)^2 - 4
81 + 36 = (9 + 2)(9 + 2) - 4
117 = 81 + 18 + 18 + 4 - 4
117 = 117